Desain Lanskap Taman Bendi sebagai Area Olahraga Outdoor dan Bermain - Muhammad Nurfauzi Ali; Akhmad Arifin Hadi (Universitas Udayana, 2022)
The increasing urban densities go parallel with the rising demand for urban green and open spaces. As one of the environmental parks, Taman Bendi in Jakarta has its green open space, which is currently provided with inadequate supporting facilities and, therefore, rarely used. This study proposes a landscape design for Bendi Park that provides public space for sports and play-related activities for the Kebayoran Lama District and its surroundings. This study uses both qualitative and quantitative methods. Data collection was carried out by conducting an online survey to study relevant community preferences, public needs, and site observation. The outputs of this research are presented in the forms of the site plan, landscape plan, elevation, section, and three-dimensional drawings. To increase public use, this study proposes that the quality of Bendi Park’s design can be obtained metaphorically by adopting the shape of bendi (horse-carriage). Regarding facilities provision, this design should be completed with playing areas, seats, jogging paths, sports facilities, signboards, directions, pedestrian bridges, animal-inviting vegetation, and vegetative barriers. Keywords: park; Bendi park; green open space; landscape; design; sports; play Abstrak Bertambahnya jumlah penduduk dengan padatnya bangunan di perkotaan menyebabkan tingginya kebutuhan ruang terbuka hijau. Taman Bendi sebagai salah satu taman lingkungan di Jakarta memiliki ruang terbuka hijau yang saat ini kondisinya belum optimal dari segi fasilitas dan penggunaannya. Penelitian ini bertujuan membuat desain lanskap Taman Bendi untuk fasilitas area olahraga dan bermain di daerah Kecamatan Kebayoran Lama dan sekitarnya. Penelitian ini menggunakan metode kualitatif melalui kuesioner daring untuk dengan memperoleh data preferensi dan kebutuhan masyarakat dan metode kuantitatif dengan pengukuran dimensi elemen lanskap di tapak. Luaran dari penelitian ini berupa gambar site plan, planting plan, potongan, dan gambar tiga dimensi. Dalam rangka meningkatkan pemanfaatan publik, penelitian ini mengajukan bahwa kualitas desain dari Taman Bendi dapat diusahakan secara metafora dengan mengadopsi bentukan kereta kuda atau bendi. Selain itu ditambahkan fasilitas area bermain, tempat duduk, jalur joging, fasilitas olahraga, papan nama, penunjuk arah, jembatan penyeberangan, vegetasi pengundang satwa dan vegetasi pembatas. Kata kunci: taman; taman bendi; ruang terbuka hijau; desain; lanskap; olahraga; bermain